2016
DOI: 10.5395/rde.2016.41.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Elemental analysis of caries-affected root dentin and artificially demineralized dentin

Abstract: ObjectivesThis study aimed to analyze the mineral composition of naturally- and artificially-produced caries-affected root dentin and to determine the elemental incorporation of resin-modified glass ionomer (RMGI) into the demineralized dentin.Materials and MethodsBox-formed cavities were prepared on buccal and lingual root surfaces of sound human premolars (n = 15). One cavity was exposed to a microbial caries model using a strain of Streptococcus mutans. The other cavity was subjected to a chemical model und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In relation to erosion, critical pH is reversely proportional to the calcium and phosphate concentrations not only in the saliva and plaque fluid, but also in the foods and drinks. Therefore, it can be even lower if acidic products contain more calcium and phosphate than biofilm fluid [73,[76][77][78]. In our study, the mean minimum pH after exposure to Coca-Cola ® was 6.3 ± 0.5, i.e., far above the theoretical critical level.…”
Section: Discussionmentioning
confidence: 54%
“…In relation to erosion, critical pH is reversely proportional to the calcium and phosphate concentrations not only in the saliva and plaque fluid, but also in the foods and drinks. Therefore, it can be even lower if acidic products contain more calcium and phosphate than biofilm fluid [73,[76][77][78]. In our study, the mean minimum pH after exposure to Coca-Cola ® was 6.3 ± 0.5, i.e., far above the theoretical critical level.…”
Section: Discussionmentioning
confidence: 54%
“…As advances in dentistry have led to significant improvements to the population's oral health, people not only live but also retain their own teeth longer. 1 This has been inevitably associated with the frequent detection of root exposure due to gingival recession and, consequently, the development of root carious lesions affecting older adults. 2 Preventing these situations saves time and money and benefits individuals' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…First, two coats of red nail varnish (Colorama Maybelline, São Paulo, SP, Brazil) were applied on the samples. Sample surfaces were divided into five parts, two of which were covered with nail varnish to act as a control area (Figure 1 [1]).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies demonstrating dentin permeability after the use of these simplified "universal" materials compared to the already established 3-step etch-and-rinse and 2-step selfetch systems are needed. It is interesting to note that this analysis is important mainly in conditions of demineralized dentin that has mineral depletion with loss of Ca and P 9 . With regard to this concept, the literature has shown that even after the photopolymerization, fluid transudation through the polymerized adhesives is observed 4,10 and that these dentin adhesives are susceptible to surface degradation by the erosive challenge.…”
Section: Introductionmentioning
confidence: 99%